2017
DOI: 10.1007/s00038-017-1043-9
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia and depression: risk factors for development of depression in male Japanese workers during 2011–2013

Abstract: A new finding was that the risk for onset of depression increased with the severity of insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…These studies also found that participants with both anxiety and depression were more likely to have difficulties in maintaining sleep than people without anxiety or depression, or with anxiety only. However, another study reported that the likelihood of newly developed depression in the future could increase with the severity of insomnia [5]. Nishitani et al [5] identified that people with at least minor insomnia symptoms (the Athens Insomnia Scale (AIS) score ≥ 1) at baseline had about 7.1 times more risk of depression than people with no insomnia symptoms at all.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies also found that participants with both anxiety and depression were more likely to have difficulties in maintaining sleep than people without anxiety or depression, or with anxiety only. However, another study reported that the likelihood of newly developed depression in the future could increase with the severity of insomnia [5]. Nishitani et al [5] identified that people with at least minor insomnia symptoms (the Athens Insomnia Scale (AIS) score ≥ 1) at baseline had about 7.1 times more risk of depression than people with no insomnia symptoms at all.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study reported that the likelihood of newly developed depression in the future could increase with the severity of insomnia [5]. Nishitani et al [5] identified that people with at least minor insomnia symptoms (the Athens Insomnia Scale (AIS) score ≥ 1) at baseline had about 7.1 times more risk of depression than people with no insomnia symptoms at all. Due to the cross-sectional design of our study, we cannot confirm a specific relationship between depression and sleep in terms of the predisposing factors, comorbid conditions, or the symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insomnia can cause daytime dysfunction, affect normal study and work, and eventually lead to a decline in the quality of life and a series of physiological and psychological diseases [ 7 ]. For example, people with insomnia are 7 times more likely to suffer from depression than healthy people [ 8 ], and insomnia will increase the risk of anxiety [ 9 ], cardiovascular diseases [ 10 , 11 ], and suicide [ 12 ]. Moreover, insomnia is associated with an increased risk for all-cause and cardiopulmonary mortality and is associated with a steeper increase in inflammation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%